Detailed kinetic modelling of H2S oxidation with presence of CO2 under rich condition. (15th March 2017) - Li, Yang; Yu, Xinlei; Li, Hongjun; Guo, Qinghua; Dai, Zhenghua; Yu, Guangsuo; Wang, Fuchen
Highlights: A detailed kinetic mechanism was developed for describing H2 S oxidation process and chemical role of CO2 . The comprehensive kinetic model has been validated via tube furnace experiment. CO2 functions as oxidant medium via CO2  + H = CO + OH under oxygen deficient condition and high temperature. Rate of production analysis was performed on studying the conversion of H2 S, H and OH radical. Abstract: This paper presents a detailed kinetic study of H2 S oxidation with presence of CO2 under fuel rich condition. Effect of CO2 reactivity on the partial oxidation of H2 S was particularly studied via tube furnace experiment and detailed kinetic analysis with CHEMKIN-PRO software. A detailed kinetic model involving 90 species and 596 reactions was developed and validated using experimental data with respect to production of H2, and conversions of CO2 and H2 S under different conditions by altering the initial gas composition temperature and residence time. In the tube furnace experiment, it was found that decomposition of H2 S and conversion of CO2 were promoted by increase in temperature while H2 production decreased and CO concentration evidently increased at temperature higher than 1450 K, which could be explained by CO2  + H = CO + OH. The degree of this reaction as features the major reactivity of CO2 is obviously dependent on residence time whilst H2 S partial oxidation proceeds much swiftly at 1473 K or higher temperature. In addition to the experiment, rate of production (ROP) analysis for H2 S, H and OH were performed by CHEMKIN-PRO. It was found for the partial oxidation of H2 S, reactions S + SH = S2  + H and SH + SH = H + HSS are important in H producing while H2 S + O = SH + OH and H2 O2 (+M) = OH + OH(+M) are key steps for OH producing. Presence of CO2 prolonged the OH production process via CO2  + H = CO + OH to the whole residence time which definitely differed from the condition without CO2 . Thereby production selectivity of SO2 and H2 O was promoted while that of H2 and S2 were degraded when CO2 was considerably present in the H2 S partial oxidation scenario.